Bioinspired Nanocomposite Hydrogels with Highly Ordered Structures. Issue 45 (23rd October 2017) - Zhao, Ziguang; Fang, Ruochen; Rong, Qinfeng; Liu, Mingjie
Abstract: In the human body, many soft tissues with hierarchically ordered composite structures, such as cartilage, skeletal muscle, the corneas, and blood vessels, exhibit highly anisotropic mechanical strength and functionality to adapt to complex environments. In artificial soft materials, hydrogels are analogous to these biological soft tissues due to their "soft and wet" properties, their biocompatibility, and their elastic performance. However, conventional hydrogel materials with unordered homogeneous structures inevitably lack high mechanical properties and anisotropic functional performances; thus, their further application is limited. Inspired by biological soft tissues with well‐ordered structures, researchers have increasingly investigated highly ordered nanocomposite hydrogels as functional biological engineering soft materials with unique mechanical, optical, and biological properties. These hydrogels incorporate long‐range ordered nanocomposite structures within hydrogel network matrixes. Here, the critical design criteria and the state‐of‐the‐art fabrication strategies of nanocomposite hydrogels with highly ordered structures are systemically reviewed. Then, recent progress in applications in the fields of soft actuators, tissue engineering, and sensors is highlighted. The future development and prospective application of highly ordered nanocomposite hydrogels are also discussed. Abstract : Biological soft tissues provide an inspiration for the fabrication of nanocomposite hydrogels with highly ordered structures by using various strategies, including magnetic fields, electric fields, mechanical strain, freeze‐casting, and self‐assembly. Based on such ordered nanocomposite structures, these hydrogels exhibit highly anisotropic properties and unique functionalities. Therefore, highly ordered nanocomposite hydrogels can serve as significant and promising soft materials for a variety of applications.